Riot Ausbruch der Verdammten - Poe, James 1921-1980; Elli, Frank (Paramount Pictures, 2023)
While the warden of a state prison is away, the isolation block erupts and 35 of the most violent criminals stage a riot and take over their portion of the prison. Cully Briston, in for five years and awaiting his eventual parole, wants no part of the riot. He impulsively gets involved, defending a prison guard and protecting him from the maniacs in the block.
Spielfilm, Orig.: USA,1969
Specials: 40-seitiges Booklet mit einem Essay von Christoph N. Kellerbach; Audiokommentar mit Dr. Gerd Naumann und Christopher Klaese; Audiointerview mit Buchautor Frank Elli; Black Cinema Radio-Spots Vol. 1: "Slaughter" und "Black Gun"; Black Cinema Trailershow; Bildergalerie
Keywords: Crime films; Thrillers; Prison riots; Prison films; Melodramas; Straflager; Gefangenenmeuterei; Flucht; Melodrama; Person of Color; Gefängnis; Thriller; Kriminalfilm; Film; DVD-Video; Blu-Ray-Disc